Polyvinylpyrrolidone-loaded Zn and ZnO nanoparticles influence Escherichia coli isolated from urinary tract infection patients - Radi, Nisreen Kaddim; Mohammed, Huda Abbas; Alwarid, Rasha Jasim; Alwarid, Rasha Jasim; Mohammed, Nada A.; Ewadh, Ruqaya Munther Jalil (Pharmakeftiki, 2025)
The biofilm formed by Escherichia coli contributes to pathogenesis through the intercellular contact within the biofilm, thereby facilitating bacterial proliferation and infection. This underscores the need for alternative antimicrobial agents with enhanced efficacy compared to traditional antibiotics. In this study, urinary tract infection (UTI)-derived E. coli isolates were assessed for susceptibility to zinc (Zn) and zinc oxide (ZnO) nanoparticles stabilised with the use of polyvinylpyrrolidone. Thirty isolates were treated with Zn and ZnO nanoparticles, and conventional polymerase chain reaction (PCR) was employed in order to detect the presence of virulence genes (phoA, VTL, and LT1). The phoA gene was detected in the majority of isolates, whereas the VTL and LT1 genes were not observed. Bacterial counts were higher in untreated controls than in nanoparticle-treated samples, with this difference being particularly pronounced in phoA-positive isolates. These findings suggest that Zn and ZnO nanoparticles hold therapeutic potential against UTI-causing E. coli strains.